Communication Barriers in Achieving Company Targets A Case Study of PT. Mantra Garmindo Sakti (Film Window Tinting Service - Baqi, Davit Al; Meltareza, Ridma (International Journal on Social Science, Economics and Art, 2025)
This study explores communication barriers at PT. Mantra Garmindo Sakti and their impact on achieving company targets. The focus is on vertical communication (between management and staff) and horizontal communication (between departments). These barriers are found to disrupt coordination, delay decision making, and reduce operational efficiency. Using a qualitative approach, data were collected through in-depth interviews with 15 participants including managers, outlet heads, technicians, and central staff and participatory observation. Thematic analysis revealed that unclear instructions, limited feedback, and fear of upward communication cause delays and task execution errors. Meanwhile, poor coordination between marketing and production teams leads to mismatches between customer demand and product availability. Participant insights highlight late and ambiguous instructions, and the lack of regular meetings across departments. To address these issues, the study recommends clearer communication tools, routine coordination meetings, and the use of Rensis Likert’s Linking Pin theory to strengthen information flow between levels. This research contributes to organizational communication studies by showing how specific internal communication failures affect target achievement in medium-sized service companies